PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJATERHADAP KINERJA KARYAWAN PADA PT. J&TCABANG BATURAJA - Wiwit Manda Sari; Darman Syafe’i; Nourma Wulanda; Palupi Indah Sari; M. Agus Kurniawan (Ekonomika, 2026)
This study aims to determine the effect of work discipline and work motivation on employee performance at PT. J&T Express Baturaja Branch. The data collection technique used in this study was through the distribution of questionnaires. The population size was 33 people. The data analysis technique used was multiple linear regression. Based on the partial analysis results, there is a positive effect of work discipline on employee performance with a t-value of 6.677. The work motivation variable has a positive effect on employee performance with a t-value of 4.392. Simultaneously, it was found that work discipline and work motivation have an effect on employee performance at PT. J&T Express Baturaja Branch with a calculated F-value 0f 157,854 > 3,32. The coefficient of determination (R2) obtained was 0.913. This indicates that the contribution of work discipline and work motivation to employee performance is 91.3%, while the remaining 8.7% is influenced by other variables outside this study, namely leadership style, work environment, workload, and job satisfaction.